Keragaman Agama, Etnis, Bahasa, dan Pembangunan Desa: Diversity of Religions, Ethnicities, Languages, and Village Development - Loria Sara Paais (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2021)
The diversity of religions, ethnicities and languages that exist in Indonesia could either be a barrier or a driver for rural development and has been receiving more attention in recent years. The purpose of this study is to analyze the long-term influence of the existence of residents with different religions, ethnicities, and daily languages in a village-on-village development. This research uses descriptive analysis and inferencing with multiple linear regression. Results of the multiple linear regression analysis show that the existence of residents of different religions and ethnicities has a positive impact on village development, but the various languages used daily have the opposite effect. In addition, the existence of credit facilities received by residents, the presence of health workers in the village, and the village topography have high enough influence on village development.